Structured exercise in patients with inflammatory bowel disease: a literature review - Achtenberg, Magdalena; Cibor, Dorota; Zwolińska-Wcisło, Małgorzata (Gastroenterology Review/Przegląd Gastroenterologiczny, 2025)
Many patients with inflammatory bowel disease (IBD) either do not respond or lose response to dedicated pharmacotherapy; therefore, physical exercise is gaining attention as a potential treatment adjunct. Recent research has highlighted the favorable relationship between physical activity and patient-reported outcomes. The reviewed studies suggest that structured exercise programs are safe and effective in the management of IBD. Yet the benefits of training trials need to be interpreted with caution due to the heterogeneity of the study methods and interventions, small sample sizes, and the absence of long-term follow-ups.